PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS FACE RECOGNITION & LOCATION BASED SERVICES (LBS) - Miqdad Zaidan Alkhair Miqdad; Titin Kristiana; Supyan Haryanto Supyan (LPPM Universitas Putera Batam, 2026)
This study aims to design and implement a web-based employee attendance system utilizing Face Recognition and Location Based Service (LBS) technologies. The system was developed to enhance the accuracy, security, and efficiency of attendance recording while facilitating monitoring processes for administrators and supervisors. The research method applied in this study is the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and evaluation stages. The results indicate that the developed system is capable of automatically verifying employee identities through facial recognition and validating attendance locations based on predefined GPS coordinates. The implementation of this system successfully reduces the potential for attendance fraud, such as proxy attendance, and accelerates the attendance data recapitulation process due to real-time and structured data storage. Furthermore, the system automatically generates daily, monthly, and overall attendance reports, thereby improving the effectiveness and efficiency of attendance management.